Coping strategies of internally displaced women in Georgia: A qualitative study. (December 2017) - Seguin, Maureen; Lewis, Ruth; Razmadze, Mariam; Amirejibi, Tinatin; Roberts, Bayard
Abstract: There is limited evidence on the coping strategies of conflict-affected civilians in low and middle income countries. The aim of this paper is to explore the coping strategies used by women internally displaced within the Republic of Georgia due to the Russo-Georgian war in 2008. We use a five-fold coping typology to examine coping strategies in the accounts of 42 Georgian women residing in internally-displaced persons settlements. Semi-structured interviews were conducted during fieldwork in Georgia from December 2012 to February 2013. Problem solving and support seeking behaviours emerged as the most-commonly-used strategies. The findings suggest interventions fostering sustainable livelihoods and robust social networks are needed to utilise the coping strategies commonly used by internally displaced women in Georgia. Highlights: A five-fold coping typology is applied to interpret the coping strategies of internally displaced women in Georgia. Internally displaced women in Georgia typically used problem-solving and support-seeking coping strategies. Interventions to support coping among internally displaced women include promoting sustainable careers and social networks.